REVISITING THE IMPERIAL IMAGINARY: NOTES ON POST 9/11 AMERICAN MEDIA - David Slocum (Soegijapranata Catholic University, 2005)
The Islamic Middle East has emerged, at least since the fist World Trade Center bombing of 1993, as the site of foremost post-Cold War antagonism with, and threat to, the West. Yet that positioning in state policy and the popular imaginary has deep roots. This paper hopes to show, that antagonism is most forcefully grounded in discourses of terrorism. The emphasis here will be on what might be term the imperial aesthetics that have shaped political and media constructions of the Middle East.